William Sturges and Henry Ellison indenture - Sturges, William; Ellison, Henry, active 1786.
Indenture between Sturges and Henry Ellison of Charleston, S.C., for sale of land.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Deeds -- South Carolina; Land tenure -- South Carolina; Charleston (S.C.) -- History